Genetic predisposition according to the age at the onset of atrial fibrillation. (19th May 2022) - Hwang, I; Hong, M; Hwang, T H; Yu, H T; Kim, T-H; Uhm, J-S; Joung, B; Lee, M-H; Jee, S H; Pak, H-N
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Ministry of Health and Welfare National Research Foundation of Korea (NRF) Background: Although atrial fibrillation (AF) is a heritable disease, multiple comorbid factors, including aging, contribute to its development. Purpose: We investigated the association between a weighted genetic risk score (wGRS) for AF and the age at onset. Methods: We included 1, 968 patients with AF (Yonsei AF Ablation cohort) and 5, 486 controls from the Korean Genome Epidemiology Study (KoGES). After 1:1 matching, 1, 416 patients and 1, 416 controls were included in the analyses. The age of AF onset was determined by the first electrocardiogram (ECG) documentation. Results: We selected nine previously reported AF-associated single-nucleotide polymorphisms (SNPs). Among nine proven AF-associated SNPs, 4 genes (PRRX1, PPFIA4, PITX2, and ZFHX3) were independently associated with the age at the onset of AF (p<0.05), but no associated genes were found in the controls. In the quartile and multivariate analyses, the lower quartile age at the onset of AF had a higher wGRS (p<0.001), and a younger age at the onset of AF was independently associated with the wGRS (β -0.29 [-0.57–0.01], p=0.045), but that association was not observed in the control cohort. Contrarily, the higher quartile of the wGRS group had a younger age of AF onset (p<0.001), and the wGRS was independently associated with the age at onset of AF (β -0.02 [-0.03–0.01], p=0.002). In the subgroup analyses, these age-wGRS associations were significant in males (p<0.001) and in those without heart failure (p<0.001) or strokes (p<0.001). Conclusions: AF-associated genetic loci significantly contributed to the age at the onset of AF, as determined by the first ECG.